Decision Decisions to Pay Professional Zakat (Study on State Civil Service Apparatus in Jambi City) - Rafiqi Rafiqi; Ary Dean Amri; Paulina Lubis (J-MAS (Jurnal Manajemen dan Sains), 2023)
Professional zakat is an obligation as Muslims to fulfill it. The intensity of the Muslim community is strongly influenced by the level of education, one's faith, knowledge and the level of welfare of a person paying professional zakat. Based on this phenomenon, efforts to increase the participation of the Muslim community need to implement strategies and policies related to the provision of more efficient zakat payment facilities and openness in its management. Various efforts have been made sometimes experiencing obstacles related to the limited resources of professional zakat services that are not yet optimal and to accommodate the Muslim community to pay professional zakat payments. Thus, application and service quality are needed that can influence the decision of civil servants to pay professional zakat. The purpose of this study is to analyze the level of participation and the factors that influence the decision to pay professional zakat. Furthermore, the data in this study were obtained from a survey of civil servants in Jambi City. The research analysis tool uses Smart PLS. This research is expected to be a basic reference for the government in formulating policies related to the optimization of professional zakat. The results showed that the determinant factors of the variables studied, the level of religiosity, utilitarian, altruism, motivation, knowledge affect the decision to pay professional zakat for state civil servants in Jambi City. Adjusted R-square value of 0.797. This means that the variables of religiosity, utilitarian, altruism, motivation, knowledge affect decisions in professional zakat by 79,7%, while the remaining 20,3% are influenced by other variables outside the model studied.